Effects of DSPP Gene Mutations on Periodontal Tissues - Jing, Zhaojun; Chen, Zhibin; Jiang, Yong (Global Medical Genetics, 2021)
Dentin sialophosphoprotein (DSPP) gene mutations cause autosomal dominantly inherited diseases. DSPP gene mutations lead to abnormal expression of DSPP, resulting in a series of histological, morphological, and clinical abnormalities. A large number of previous studies demonstrated that DSPP is a dentinal-specific protein, and DSPP gene mutations lead to dentin dysplasia and dentinogenesis imperfecta. Recent studies have found that DSPP is also expressed in bone, periodontal tissues, and salivary glands. DSPP is involved in the formation of the periodontium as well as tooth structures. DSPP deficient mice present furcation involvement, cementum, and alveolar bone defect. We speculate that similar periodontal damage may occur in patients with DSPP mutations. This article reviewed the effects of DSPP gene mutations on periodontal status. However, almost all of the research is about animal study, there is no evidence that DSPP mutations cause periodontium defects in patients yet. We need to conduct systematic clinical studies on DSPP mutation families in the future to elucidate the effect of DSPP gene on human periodontium.
Keywords: dentin sialophosphoprotein; genetic mutations; periodontal defects